Intersectionality of Socioecological Factors Associated With Cognitive Function Among Older Women With HIV in the United States: A Structural Equation Model Analysis Using Data From the Women's Interagency HIV Study. (12th January 2023) - Njie-Carr, Veronica P. S.; Zhu, Shijun; Stafford, Kristen A.; Tong, Weiqun; Plankey, Michael; Sharma, Anjali; Milam, Joel; Cohen, Mardge; Diaz, Monica M.; Rubtsova, Anna A.; Fischl, Margaret A.; Konkle-Parker, Deborah; et al.
Abstract: Increased life expectancy of people with HIV has health implications including the intersection of the long-term use of antiretroviral treatment, inflammatory events, and age-related immunosenescence. In a cross-sectional study utilizing using the Socio-Eecological Model, we identified pathways of cognitive function (CF) among 448 women with HIV, 50 years and older. A structural equation model showed the direct effects of mood (β = −0.25, p < .01), comorbidities (β = −-0.13, p < .05), race (β = −-0.13, p < .05), and abuse (β = 0.27, p < .001) on the latent variable CF. Substance and alcohol use, depressive symptoms, cigarette smoking, and the number of comorbidities are important considerations when designing interventions utilizing using a multi-level and intersectional lens to maximize positive CF outcomes.